Tactile tissue characterisation by piezoelectric systems - Stroop, Ralf; Uribe, David Oliva; Martinez, Melisa Orta; Brökelmann, Michael; Hemsel, Tobias; Wallaschek, Jörg (Journal of Electroceramics)
For devices having non-linear contact, load plays a fundamental role. Variations in the characteristics of the load cause change in eigenfrequency and amplitude of the vibration. In most technical applications, this unwanted behaviour is cancelled by the use of control algorithms. However, multiple applications, like bond quality monitoring or chemical and pressure sensors, have found that the load may be characterised by interpreting the change in characteristics of a resonant vibrating device used as a sensor. Surgical resection of tumours is a very difficult task. After localising the tumour by the use of imaging techniques, the resection demands the surgeon to decide where and what to resect based on visual and tactile differentiation of tumour and healthy tissue. Exactness of this process could be enhanced if we can provide the surgeon with a device capable of evaluating mechanical characteristics of the tissue much more accurately than the surgeon himself can do. As the mechanical characteristics of tumour and healthy tissue differ but slightly, the task is to design a system with high sensitivity. Therefore, we have developed a resonant actuator-sensor that allows the differentiation among distinct media that have similar mechanical characteristics to tumour and healthy tissue using a piezoelectric bimorph. The design is based on the detection and evaluation of frequency shift and amplitude variation of the fundamental and higher harmonics using one layer for the resonant excitation of vibration and the other one as the sensing element.
Keywords: Piezo ceramics; Bimorph; Tactile sensor; Tumour tissue